Susceptibility of Clostridium difficile to the food preservatives sodium nitrite, sodium nitrate and sodium metabisulphite. (February 2016) - Lim, Su-Chen; Foster, Niki F.; Riley, Thomas V.
Abstract: Clostridium difficile is an important enteric pathogen of humans and food animals. Recently it has been isolated from retail foods with prevalences up to 42%, prompting concern that contaminated foods may be one of the reasons for increased community-acquired C. difficile infection (CA-CDI). A number of studies have examined the prevalence of C. difficile in raw meats and fresh vegetables; however, fewer studies have examined the prevalence of C. difficile in ready-to-eat meat. The aim of this study was to investigate the in vitro susceptibility of 11 C. difficile isolates of food animal and retail food origins to food preservatives commonly used in ready-to-eat meats. The broth microdilution method was used to determine the minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) for sodium nitrite, sodium nitrate and sodium metabisulphite against C. difficile . Checkerboard assays were used to investigate the combined effect of sodium nitrite and sodium nitrate, commonly used in combination in meats. Modal MIC values for sodium nitrite, sodium nitrate and sodium metabisulphite were 250 μg/ml, >4000 μg/ml and 1000 μg/ml, respectively. No bactericidal activity was observed for all three food preservatives. The checkerboard assays showed indifferent interaction between sodium nitrite and sodium nitrate. This study demonstrated that C. difficile can survive in the presence of food preservatives at concentrations higher than the current maximum permitted levels allowed in ready-to-eat meats. The possibility of retail ready-to-eat meats contaminated with C. difficile acting as a source of CDI needs to be investigated. Highlights: The susceptibility of Clostridium difficile to food preservatives was determined. MICs of sodium nitrite, sodium nitrate and sodium metabisulphite were 250 μg/ml, >4000 μg/ml and 1000 μg/ml, respectively. The MICs of food preservatives against C. difficile were higher than their maximum permitted level in ready-to-eat meats. C. difficile can survive in high concentrations of food preservatives. The prevalence of C. difficile in ready-to-eat meats requires investigation.